Examining the Effects of Integrating Anxiety Management Instruction Within a Reading Intervention for Upper Elementary Students With Reading Difficulties. (September 2022) - Vaughn, Sharon; Grills, Amie E.; Capin, Philip; Roberts, Greg; Fall, Anna-Mária; Daniel, Johny
We present findings from the first cohort of third- and fourth-grade students with reading difficulties (128 students from 31 classrooms) who participated in a 2-year intervention examining the effects of a reading intervention with and without anxiety management. Using a randomized controlled trial, students were assigned to one of three conditions: (a) small-group reading intervention with anxiety management instruction (RANX), (b) small-group reading intervention with math fact practice (RMATH), and (c) business-as-usual (BAU) comparison condition (no researcher provided treatment). Personnel from the research team provided participants in the RANX and RMATH the same reading intervention with the variation in the two treatments being whether the same amount of time per lesson was allocated to anxiety management (RANX) or practicing math facts (RMATH). Students in the RANX significantly outperformed students in the BAU on reading comprehension (effect size [ES] = 1.22) and students in the RMATH outperformed BAU on reading comprehension (ES = 0.77). Groups did not differ significantly on other reading outcomes. Reading anxiety moderated the main effect of the RANX intervention on the Test of Word Reading Efficiency (TOWRE) word reading when contrasted against the BAU group, indicating a significant difference favoring RANX where treatment's effect decreased by 0.94 units (about 1 point on the outcome) on word reading for each additional point increase in reading anxiety.